2015
DOI: 10.1007/s00267-015-0566-1
|View full text |Cite
|
Sign up to set email alerts
|

Hot Spots and Hot Times: Wildlife Road Mortality in a Regional Conservation Corridor

Abstract: Strategies to reduce wildlife road mortality have become a significant component of many conservation efforts. However, their success depends on knowledge of the temporal and spatial patterns of mortality. We studied these patterns along the 1000 Islands Parkway in Ontario, Canada, a 37 km road that runs adjacent to the St. Lawrence River and bisects the Algonquin-to-Adirondacks international conservation corridor. Characteristics of all vertebrate road kill were recorded during 209 bicycle surveys conducted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 47 publications
1
43
0
1
Order By: Relevance
“…The reason as to why amphibians in general appear to be more vulnerable to wildlife-vehicle collisions than other taxa has been related to their ecology and life history. Three studies confirmed that road mortality of amphibians peaked as they attempted to cross roads during their migration in the spring from terrestrial hibernacula to aquatic breeding habitats [11,12,14]. These studies recommended that mitigation could be implemented during this seasonal activity period in order to reduce amphibian road-mortality rates; however, a study conducted on Fowler's toad (Anaxyrus fowleri) cautioned that road mortality may not always be limited to seasonal migrations [15].…”
Section: Direct Impacts Of Roads On Wildlifementioning
confidence: 99%
See 2 more Smart Citations
“…The reason as to why amphibians in general appear to be more vulnerable to wildlife-vehicle collisions than other taxa has been related to their ecology and life history. Three studies confirmed that road mortality of amphibians peaked as they attempted to cross roads during their migration in the spring from terrestrial hibernacula to aquatic breeding habitats [11,12,14]. These studies recommended that mitigation could be implemented during this seasonal activity period in order to reduce amphibian road-mortality rates; however, a study conducted on Fowler's toad (Anaxyrus fowleri) cautioned that road mortality may not always be limited to seasonal migrations [15].…”
Section: Direct Impacts Of Roads On Wildlifementioning
confidence: 99%
“…For example, of the 27 studies that investigated road-related mortality in up to three related species, 15 studies involved species of conservation concern, while the remaining 12 studies considered the common and widespread species that are often reported in wildlife-vehicle collisions. Amphibians appeared to generate the most concern, with a number of multiple-taxa studies finding that they made up the highest percentage of roadkills (as much as 80% recorded, [9][10][11][12]). Studies warn that with many amphibian populations already declining globally any additional nonnatural mortality could further impact population persistence [13].…”
Section: Direct Impacts Of Roads On Wildlifementioning
confidence: 99%
See 1 more Smart Citation
“…As recommended for roads, railway surveys should be carried out early in the morning (to reduce scavenging, but see also sources of bias below), preferably by two experienced observers walking at specified railway stretches, one on each side of the rail (Peña and Llama 1997), and covering a 10 m sight strip whenever logistically possible. The use of a vehicle could be a better choice if parallel dirty roads exist (at least on one side), and in cases where the surveyed stretch is too long (>10 km), but their detectability as proved to be lower (Garrah et al 2015). Once a carcass is found, and depending on its state of decay, several variables should be recorded: species, age, sex, GPS location, time of day, weather conditions, position on the railway (verges, between lines, rock ballast, etc.…”
Section: Estimating the Number Of Casualties On Railwaysmentioning
confidence: 99%
“…The nearest neighbour hierarchical clustering identifies groups of points based on "nearest-neighbor-method" criteria (Gomes et al 2009). Finally, the Getis-Ord Gi* statistic identifies hotspots by adding the number of casualties associated with a given segment of the road to the casualties of its neighboring segments, and compares that value with an overall expected distribution (Garrah et al 2015). Integrating the information on rail sectors with high mortality rates with GIS mapping tools leads to the identification of the locations where mitigation measures (drift fences, rail passages, traffic regulation, etc.)…”
Section: How To Describe and Evaluate Hotspots Of Mortalitymentioning
confidence: 99%